Criminal Law Protection On Online Victims Of Victims - Harefa, Safaruddin (Veteran Law Review, 2019)
This study aims to find out and analyze how criminal law protection for victims of online businesses. This study uses a juridical normative law research with secondary legal materials, namely analyzing the study of legislation and cases. The results of the research that the authors get are that criminal legal protection against victims of online business crime in accordance with existing laws and regulations should guarantee the existence of victims' rights from online businesses. The rights that must be obtained by online business victims are contained in Law Number 31 Year 2014 concerning Amendments to Law Number 13 Year 2006 concerning Witness and Victim Protection and Law Number 11 Year 2008 Information and Electronic Transactions (ITE ) That the rights that have been guaranteed have not run optimally are carried out because the rules governing the protection of consumers of online businesses have not been detailed in a Legislation and do not provide space for victims to obtain criminal legal protection